Retelling Fantasy Story Text Learning with Creative Productive Model based on Learning Styles of Seventh Graders (Seloka: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2020)
Retelling fantasy story text activity is productive language activity. Therefore, there is a need of appropriate learning model to students’ learning styles. This research aims to explain effectiveness of retelling fantasy story text learning with creative productive model based on the seventh graders’ learning styles. The used method in this research is quasi-experimental design with techniques of collecting data by using instruments of retelling fantasy story test, learning style test, and documentation. Normality test of the data used Kolmogorov-Smirnov. Homogeneity data test used Levene test. Hypothesis test used paired sample t-test. All test used SPSS 2.0 program test. The conclusion of this research showed that implementation of creative productive model was effective to use in the learning based on learning styles of the seventh graders. Retelling fantasy story learning used creative productive model was found to be more effective when it was implemented on intuitive learning style typed students than sensible learning style typed students. Theoretically, this research was expected to contribute in retelling fantasy story learning.